Sociology of Education or Education without Sociology? Effort of a Science-Based Research - Garold E. Zborovsky (National Research Mordova State University, 2022)
Introduction. As the number of scientific publications on the problems of education increases, it is increasingly possible to detect the desire of authors to consider them as sociological. Meanwhile, many of them do not meet the requirements for articles based on data from sociological empirical studies. In this regard, there is a need to separate publications of different nature, orientation, and functions, which focus on the problems of education. The purpose of the article is to analyze the criteria for attributing publications to the disciplinary field of sociology of education and to identify their specifics. Achieving this goal will clarify the issue of trust in scientific publications, research results, and the appropriateness of their use for making managerial decisions in the field of education. Materials and Methods. The object of the research is scientific journals that publish articles on education issues on a regular basis, including under the heading "Sociology of Educationˮ. The sample includes relevant publications and publications in them for the last 5 years. The subject of the study was the content of publications that were classified either by publications or by the authors of articles as sociological. The main methods used were content analysis and historical and sociological analysis. Results. The specifics of the subject field of sociology of education and the trends of its formation and development are determined. The main criteria for determining the differences of publications in the field of sociology of education are formulated. Discussion and Conclusion. The article is devoted to the experience of science-based research. In the process of discussing the results obtained, attention is drawn to the specific nature, special tasks and functions of sociological research and publications in the field of education. The importance of these results for improving the quality of empirical studies of education and publications based on them, as well as the possibility of using them to solve its practical problems, is shown.